Religious Pluralism In Tafsir Al-Mizan: Thabathaba'i Perspective And Its Relevance In Multicultural Indonesia - Gafar, Lalu Abdul; Nurusshobah, Nurusshobah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
Indonesia's diverse society, with its multitude of ethnicities, religions, and cultures, stands as both a profound asset and a significant challenge. While this diversity is a source of immense social wealth, it can also lead to conflict if not properly managed. Religious tolerance plays a central role in ensuring social harmony, as religion often serves as a strong identity marker that may create divisions or competition among groups. In this context, Islamic moderation presents a peaceful way to combat radicalism and extremism. This study examines the views of Allama Tabatabai in his al-Mizan fi Tafsir al-Quran regarding religious pluralism, exploring its relevance to fostering tolerance and social unity in Indonesia. Using a qualitative, library-based research approach, data was gathered from various sources, including Qur'anic commentaries, academic journals, and related literature. The findings suggest that while religious pluralism can be a sensitive issue, it also offers a foundation for strengthening social tolerance. Thabathaba’i argues that salvation in the afterlife is not determined solely by one’s religion but by faith in God, belief in the Day of Judgment, and good deeds. This inclusive perspective offers a framework for understanding religious differences in Indonesia. Ultimately, the research demonstrates that understanding religious pluralism through Tabatabai's interpretation can promote a more harmonious and tolerant society, where Islamic moderation and respect for diversity are key to building social unity amid Indonesia’s diverse and globalized environment. This research is innovative in applying Tabatabai's thoughts to the Indonesian context, highlighting their potential for enhancing social harmony amidst diversity.